Production Risk of Groundfish In UD. XY Bengkulu City: Failure Mode and Effects Analysis (FMEA) - Julian Rahmadi; M. Mustopa Romdhon; Reswita Reswita (Badan Penerbitan Fakultas Pertanian (BPFP), 2020)
One of the fish processing units in Bengkulu City is UD.XY, which is located in Sumber Jaya Urban Village, Kampung Melayu Sub-district, Bengkulu City. The seafood processing product is groundfish made of fresh mackerel. Analysis of production risk is an important aspect of ensuring the survival of a business. The production risk was 15% in one production, so the selling price lowered and reprocessing was impossible. The risk comes from the material, production process, and final product. The present study was aimed to analyze the production risk of groundfish. The analysis method was FMEA. The research result showed that the highest risk was poor fish supply, poor groundfish products, and competing groundfish products.